Social impact of ecotourism on the behavior of students on educational field trips to Makiling Botanic Gardens in the University of the Philippines Los Banos - Roslin, Ma Anya Yasmin A.; Maga, Janet P.; Rosales, Agnes B.; Tapay, Nenita E.; Cereno, Roberto (2009)
The Makiling Botanic Gardens (MBG) in the science community of UPLB is one of the notable destinations of educational field trips. The increasing number of such trips calls for a better understanding of tourists' expectations and source of satisfactions. A visit to MBG as major spot for ecotourism provides student with leaning that is beneficial to the environment. The survey used as structured interview schedule as tool for gathering data. Descriptive statistics in the form of frequency counts, percentages and means was used to analyze the responses. The Pearson correlation was used to determine relationships between sociodemographic profile on one hand and the importance of visits and satisfaction of ecotourism benefits on the other hand. The scenery and opportunities for experiencing nature, admiring the tropical forest ecosystem and outdoor recreation activities were the benefits most sought by the student visitors and also the ones from which they derived the most satisfaction.
Keywords: Ecotourism; Makiling Botanical Gardens